Аналіз розробки концепт арт персонажів у стилі Darkest Dungeon - Чернюк, М. А. (ХНУРЕ, 2023)
Working on characters in the style of Darkest Dungeon requires the artist to combine technical drawing skills with creativity and attention to detail. It is important to create characters that will be remembered by players and deeply fit into the atmosphere of the game. In general, working as a concept artist on a Darkest Dungeon-style game requires a talent for drawing and a flair for creating atmospheric artwork, as well as the ability to work in a team and interact with other members of the development team. This paper examines the steps to be taken in order to start working on the characters in such a project.
Keywords: персонаж; Darkest Dungeon